Exploring the mechanism of Synechococcus sp. XM-24 in gastric cancer treatment via network pharmacology and molecular docking - Li, Jiayi; Ma, Yamei; Guo, Longzhi; Liu, Junhong; Li, Lin (PloS one, 2025)
We investigated the potential molecular mechanisms of Synechococcus sp. XM-24 affect gastric cancer (GC) development. Furthermore, this study aimed to provide a theoretical basis for developing novel therapeutic drugs for treating GC. The interactions between Synechococcus sp. XM-24 and targeted proteins in GC were analyzed through network pharmacology and molecular docking. Molecular dynamics (MD) simulation of the protein-small molecule complex obtained from molecular docking were performed using the Gromacs v2022.03 software. Based on the intersecting target genes of Synechococcus sp. XM-24 and GC, Gene Ontology function and Kyoto Encyclopedia of Genes and Genomes analyses were performed to obtain the associated biological processes (BP), cellular components (CC), molecular functions (MF), and signal transduction pathways. In total, 609 intersecting targets were identified between Synechococcus sp. XM-24 and GC, with nine key target genes (AKT1, ALB, IL1B, SRC, STAT3, EGFR, HSP90AA1, ESR1, and BCL2) being identified as active components of Synechococcus sp. XM-24. These key target genes were involved in 1,028 BP, 110 CC, 312 MF, and 200 signaling pathways. The enriched signaling pathways mainly included the cancer pathway, metabolic pathway, phosphatidylinositol 3-kinase-protein kinase B(PI3K-AKT) signaling pathway, and Rat sarcoma signaling pathway. Additionally, molecular docking analysis revealed strong binding activities between 10 active components of Synechococcus sp. XM-24, including methyl vaccenate, allyl methallyl ether, and 11-octadecenoic acid, with key target proteins such as albumin (ALB). MD simulations demonstrated a stable binding of ALB and methyl vaccenate, with a binding free energy of -48.39 kcal/mol. Overall, the findings of this study reveal the therapeutic potential of Synechococcus sp. XM-24 in the prevention and treatment of GC, along with providing a theoretical basis for further development in GC treatment employing Synechococcus sp. XM-24.